EFFECT OF TRINEXAPAC-ETHYL ON GROWTH AND YIELD OF SUGARCANE - FARIA,A. T. (2015)
ABSTRACT Growth regulators can be used to further retard or inhibit vegetative growth. In this sense, the objective of this study was to determine the effects of age and number of trinexapac-ethyl applications on the growth and yield of sugarcane. The experiment was in a randomized complete block design with four replications. The treatments were in a 3 x 2 + 2 factorial arrangement, where factor A corresponded to the application times of the plant growth regulator (120, 200 and 240 days after bud burst (DAB) of sugarcane) and factor B to the number of applications (one or two applications). In addition, two controls (one with three applications and another application without the regulator) were added. The application of trinexapac-ethyl decreased the number and the distance between buds, height, root volume and sugarcane yield. The sequential application (2 or 3 times) induced an increase in stem diameter and three applications of the product increased the number of plant tillers. The use of growth regulators applied at 240 DAB has reduced plant height, however without changing the number of buds. It can be concluded that trinexapac-ethyl changes sugarcane growth and yield, regardless of season and number of applications.